Biodegradation Mechanisms of Iron Oxide Monocrystalline Nanoflowers and Tunable Shield Effect of Gold Coating. Issue 16 (3rd May 2014) - Javed, Yasir; Lartigue, Lénaic; Hugounenq, Pierre; Vuong, Quoc Lam; Gossuin, Yves; Bazzi, Rana; Wilhelm, Claire; Ricolleau, Christian; Gazeau, Florence; Alloyeau, Damien
<x xml:space="preserve">Abstract</x> Understanding the relation between the structure and the reactivity of nanomaterials in the organism is a crucial step towards efficient and safe biomedical applications. The multi‐scale approach reported here, allows following the magnetic and structural transformations of multicore maghemite nanoflowers in a medium mimicking intracellular lysosomal environment. By confronting atomic‐scale and macroscopic information on the biodegradation of these complex nanostuctures, we can unravel the mechanisms involved in the critical alterations of their hyperthermic power and their Magnetic Resonance imaging T1 and T2 contrast effect. This transformation of multicore nanoparticles with outstanding magnetic properties into poorly magnetic single core clusters highlights the harmful influence of cellular medium on the therapeutic and diagnosis effectiveness of iron oxide‐based nanomaterials. As biodegradation occurs through surface reactivity mechanism, we demonstrate that the inert activity of gold nanoshells can be exploited to protect iron oxide nanostructures. Such inorganic nanoshields could be a relevant strategy to modulate the degradability and ultimately the long term fate of nanomaterials in the organism.